Exploring Associations Lipid Profiles, Body Composition, Anthropometry, and Osteoarthritis Index - Diana Dinali; Muhammad Fikri Dzakwan; Steve Geraldo Bustam; Shirly Gunawan; Alexander Halim Santoso; Yohanes Firmansyah (Biomedical Journal of Indonesia, 2026)
Introduction. Osteoarthritis (OA) is a joint disorder and is considered one of the leading causes of disability worldwide. It is commonly associated with aging and characterized by chronic pain, joint stiffness, and limitations in daily activities. This study aimed to evaluate the association between lipid profile and body composition with the severity of OA, as measured by the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score. Methods. This cross-sectional study involved 67 community-dwelling older adults. Assessments included fasting lipid profiles (HDL, LDL, total cholesterol, Apo A, Apo B, and triglycerides), body fat distribution and muscle mass, anthropometric measurements (body mass index, waist circumference, and hip circumference), and handgrip strength. Associations between variables were analyzed using Spearman’s correlation test with a significance level of 5%. Results. Correlation analysis demonstrated associations between lipid profile levels and worsening OA symptoms. Higher Apo B levels were associated with increased trunk fat (r=0.47, p<0.001) and greater joint pain (r=0.35, p=0.004). Lower HDL levels were associated with increased visceral fat (r=−0.37, p=0.002) and greater joint stiffness (r=0.26, p=0.038). Greater upper extremity muscle mass was associated with less severe pain (r=−0.38, p<0.001), while higher body mass index and waist circumference were associated with higher WOMAC scores (r=0.32, p=0.009). Conclusion. These findings support the concept that OA is a systemic condition influenced by metabolic and biomechanical pathways. OA management should therefore include metabolic control, optimization of body composition, and routine monitoring of lipid profiles and anthropometric indices as part of non-pharmacological therapy and preventive strategies.